18F-Radiolabeled Translocator Protein (TSPO) PET Tracers: Recent Development of TSPO Radioligands and Their Application to PET Study - Truong Giang Luu; Hee-Kwon Kim (Pharmaceutics, 2022)
Translocator protein 18 kDa (TSPO) is a transmembrane protein in the mitochondrial membrane, which has been identified as a peripheral benzodiazepine receptor. TSPO is generally present at high concentrations in steroid-producing cells and plays an important role in steroid synthesis, apoptosis, and cell proliferation. In the central nervous system, TSPO expression is relatively modest under normal physiological circumstances. However, some pathological disorders can lead to changes in TSPO expression. Overexpression of TSPO is associated with several diseases, such as neurodegenerative diseases, neuroinflammation, brain injury, and cancers. TSPO has therefore become an effective biomarker of related diseases. Positron emission tomography (PET), a non-invasive molecular imaging technique used for the clinical diagnosis of numerous diseases, can detect diseases related to TSPO expression. Several radiolabeled TSPO ligands have been developed for PET. In this review, we describe recent advances in the development of TSPO ligands, and 18F-radiolabeled TSPO in particular, as PET tracers. This review covers pharmacokinetic studies, preclinical and clinical trials of 18F-labeled TSPO PET ligands, and the synthesis of TSPO ligands.